2017
DOI: 10.1177/016146811711901310
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Hand in Hand: Adaptive Teaching and Self-Regulated Learning

Abstract: This article presents case studies of two novice teachers and their mentors who, without formal knowledge of self-regulation theory, established a classroom environment that promoted self-regulated learning. This case was drawn from a larger descriptive study of novice teachers learning to integrate a student-centered visual literacy instructional approach into their literacy curriculum. This visual literacy approach requires teachers to adapt their teaching to students by building on students’ responses to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…der Kompetenzentwicklung reduziert die Lehrkraft schrittweise den Grad der Unterstützung und überträgt im Sinne des Scaffolding (van de Pol et al 2010) zunehmend Verantwortung für den eigenen Lernprozess an die Schüler*innen. Dabei passt nicht nur die Lehrkraft die Unterstützung an die Schüler*innen an, sondern auch die Schüler*innen passen sich über die Zeit in ihrem Lernverhalten an (Corno 2008;Randi 2017).…”
Section: Was Ist Adaptiver Unterricht?unclassified
“…der Kompetenzentwicklung reduziert die Lehrkraft schrittweise den Grad der Unterstützung und überträgt im Sinne des Scaffolding (van de Pol et al 2010) zunehmend Verantwortung für den eigenen Lernprozess an die Schüler*innen. Dabei passt nicht nur die Lehrkraft die Unterstützung an die Schüler*innen an, sondern auch die Schüler*innen passen sich über die Zeit in ihrem Lernverhalten an (Corno 2008;Randi 2017).…”
Section: Was Ist Adaptiver Unterricht?unclassified
“…Chen, W. et al qualitatively investigated how knowledge related to collaborative writing among second language students affects the process of collaborative writing based on metacognitive theories and found that knowledge of collaborative writing affects collaboration in three stages: planning, writing, and revising [12]. Randi, J. et al illustrated how a novice instructor integrated a student-centered approach to teaching visual literacy into their literacy courses in a research project that provided context and reference for the dynamic relationship between teaching learning and research [13]. Barari, N. et al conducted an in-depth analysis and examination of learning theories in an e-learning course at Shahid Beheshti University and found that course activities based on behaviorist learning theories were higher, through both qualitative research methods and content analysis, at 51% and fewer based on new learning theories at 15% [14].…”
Section: Introductionmentioning
confidence: 99%